Turbin Crossflow untuk PLTMH di Sungai Karuah, Kelurahan Lambung Bukit, Kec Pauh, Padang - Nota Effiandi; Yuliarman Yuliarman; Ichlas Nur (Politeknik Negeri Padang, 2023)
Utilization of electrical energy has been applied in almost all fields of life. One of them is the use of electricity to repel plantation pests. In the hills of Batu Busuk, around the Padang Karuah River, Kel Lambung Bukit, Kec. Pauh, Padang is one of the communities that has implemented the application. The people who are gardening there have worked together in making a Micro Hydro Power Plant (PLTMH) type waterwheel with a power of 1 kW with the current condition has been damaged and can not be used anymore. Seeing the potential of water owned according to the results of the field survey with a flowrate of 100 L / s and a head of 5 m, the use of crossflow turbines is one type of turbine that is suitable for replacing a windmill that has been damaged with a power generated of 3.7 kW. The crossflow turbine has an outer diameter of runner (D1) 0.3 m, runner width (L) 0.2 m and the number of blades (z) 28 pieces. With the use of the crossflow turbine, the potential of water will be maximally utilized.